+0  
 
0
41
1
avatar+40 

Using row notation, solve:

10(e-4)=20(f-e)

20(f-4)=10(e+f)

 Jan 26, 2021

Best Answer 

 #1
avatar+382 
+1

Hi GR0001!

 

10(e - 4) = 20(f - e)

10e - 40 = 20f - 20e

e - 4 = 2f - 2e

3e = 2f + 4

 

20(f - 4)=10(e+f)

2(f - 4) = e + f

2f - 8 = e + f

f = e + 8

 

3e = 2(e + 8) + 4

e = 20

f = 20 + 8

f = 28. 

 

So e = 20 and f = 28. 

I hope this helped. :)))

 

=^._.^=

 Jan 26, 2021
 #1
avatar+382 
+1
Best Answer

Hi GR0001!

 

10(e - 4) = 20(f - e)

10e - 40 = 20f - 20e

e - 4 = 2f - 2e

3e = 2f + 4

 

20(f - 4)=10(e+f)

2(f - 4) = e + f

2f - 8 = e + f

f = e + 8

 

3e = 2(e + 8) + 4

e = 20

f = 20 + 8

f = 28. 

 

So e = 20 and f = 28. 

I hope this helped. :)))

 

=^._.^=

catmg Jan 26, 2021

60 Online Users

avatar
avatar
avatar
avatar